Factors affecting maize (Zea mays L.) sensitivity to acetochlor - Mphundi, Patricia Makuzana (University of the Free State, 2009)
A number of the commercially available maize cultivars were screened in order to establish their tolerance to acetochlor. These cultivars demonstrated significant differences in their tolerance, with some cultivars being tolerant and others sensitive to the herbicide. The cultivar PAN6Q521R was the most tolerant and DKC 73-76R was the most sensitive, while most other cultivars were intermediate in their sensitivity. This indicates that maize tolerance to acetochlor is genetically controlled. The influence of planting depth on maize tolerance to acetochlor was investigated using these two cultivars. Both cultivars were found to be more sensitive as the planting depth increased to 45 mm. However, seedlings of DKC 73-76R exhibited more phytotoxicity than PANQ6521R at all planting depths. The effect of seed size on acetochlor tolerance could not be determined with any clarity. Cultivar sensitivity to the herbicide as well as seed shape appeared to also play a role. In DKC 73-76R it appeared as though large flat seeds produced plants more tolerant to acetochlor than smaller flat seeds. The effect of soil type on acetochlor phytotoxicity on a tolerant (PANQ6521R) and sensitive (DKC 73-76R) maize cultivar was examined in two trials, one using an average application rate on all soils, and the second utilizing the recommended application rates for each soil. Acetochlor activity was found to be lowest on the clay loam soil (38% Clay) and highest on the sandy soil (8% Clay) in the first case, with severe phytotoxicity occurring on the latter soil. In the second trial bioactivity was similar on all soils, although greater on the sand. This indicated that the recommended application rate on sandy soils might need adjustment. The influence of temperature on maize tolerance to acetochlor was investigated at suboptimal (15/8oC), optimal (25/18oC) and supra-optimal (35/28oC) temperature regimes (day/night temperature respectively). Seedling growth of both cultivars was inhibited significantly by acetochlor at the optimum temperature regime (25/18oC). All results confirmed that DKC 73-76R was more sensitive to acetochlor than PAN6Q521R.

‘n Aantal mielie cultivars wat in die handel beskikbaar is, is getoets vir hulle sensitiwiteit teenoor asetochlor. Betekenisvolle verskille m.b.t. sensitiwiteit van hierdie cultivars is gevind, met sommige cultivars wat verdraagsaam was teenoor die onkruiddoder, terwul ander sensitief was. Die cultivar PAN6Q521R het die hoogste verdraagsaamheid getoon, terwyl DKC 73-76R die sensitiefste was. Die meeste ander cultivars was intermediêr in hulle verdraagsaamheid. Hierdie gee ‘n aanduiding dat die verdraagsaamheid van mielies teenoor asetochlor geneties beheer word. Die invloed van plantdiepte op die sensitiwiteit van mielies teenoor asetochor is ondersoek met beide cultivars. Dit is gevind dat beide cultivars meer sensitief geraak het na mate die plantdiepte na 45 mm toegeneem het. Saailinge van DKC 73-76R het grootter fitotoksisiteit getoon as die van PAN6Q521R by alle plantdieptes. Die invloed van saadgrootte op asetochlor verdraagsaamheid kon nie met sekerheid bepaal word nie. Cultivar sensitiwiteit teenoor die onkruiddoder asook saadvorm het skynbaar ‘n rol hier gespeel. Dit blyk dat groot plat sade saailinge geproduseer het wat meer verdraagsaam teenoor asetochlor was as die van klein plat sade in DKC 73-76R. Die invloed van grondtipe op asetochlor fitotoksisiteit op ‘n verdraagsame (PAN6Q521R) en sensitiewe (DKC 73-76R) cultivar is in twee proewe getoets. Die eerste proef het ‘n gemiddelde toedienings hoeveelheid van die onkruiddoder op alle gronde gebruik, terwyl die tweede proef die aanbevole toedieningshoeveelheid vir elke grond gebruik het. Asetochlor aktiwiteit was die laagste op die klei-leem grond (38% klei) en die hoogste op die sand grond (8% klei) in die eerste proef, en ernstige fitotoksisiteit het op die sandgrond voorgekom. Bioaktiwiteit was soortgelyk op alle gronde in die tweede proef, alhoewel dit strawwer was op die sandgrond. Hierdie het ‘n aanduiding gegee dat die aanbevole toedieningspeil op die sanderige grond moontlik aangepas behoort te word. Temperatuur se invloed op die verdraagsaamheid van mieliecultivars teenoor asetochlor is getoets by sub-optimale (15/8°C), optimale- (25/18°C) en supra-optimale (35/28°) temperatuur regimes (dag-/nagtemperatuur). Saailinggroei van beide cultivars is betekenisvol onderdruk deur die onkruiddoder by die optimale temperatuur regime. Alle resultate het aangedui dat die cultivar DKC 73-76R meer sensitief is teenoor asetochlor as PAN6Q521.
Dissertation (M.Sc.Agric. (Soil, Crop and Climate Science))--University of the Free State, 2009
Keywords: Corn -- Weed control; Herbicides -- Environmental aspects; Tolerance; Temperature; Seed size; Planting depth; Maize cultivar; Phytotoxicity; Clay percentage; Acetochlor